University industries centre management system (UICMS) - Nur Hazlinda, Azmi (2009)
Management Information System (MIS) is a process or a system that is capable to computerize data.Through this system all data can be saved in a systematic way.All saving process is efficient.This processes can easily saved and data retrieval is fast and efficient. University Industries Centre Management System (UICMS) uses all the attributes mentioned above.In current process,there is no system for saving the information for UMP University Industries Centre.This system will allow all data to be computerized and saved in a systematic way.